Game-based educational media and associative skills in kindergarten students' early reading and writing development - Salamah, Salamah; Sarjiyem, Sarjiyem (LPMPP Universitas Negeri Yogyakarta, 2025)
This study investigated whether children's association skills and engagement with literate media, toys, games, and activities influence their early reading and writing abilities in kindergarten. The study included 60 participants selected by cluster random sampling using a 2 x 2 factorial design. The results indicated that children with literate media scored higher in early reading and writing abilities than those with non-literate media. Fourth, youngsters with high association skills who play with literate media score better than youngsters with high association skills who play with nonliterate media. Children with high association skills also demonstrated better early reading and writing abilities than those with low association skills. The study found a significant interaction between association skills and media, influencing early reading and writing abilities differently. The study emphasizes the importance of incorporating literate media and activities promoting association skills in early childhood education to enhance children's reading and writing abilities. It also highlights the need for teachers and parents to consider individual differences in association skills when selecting media and activities for young children. Both literate and non-literate media have an important impact when combined with different association skills, influencing children's early reading and writing abilities.